2018
DOI: 10.1111/joor.12706
|View full text |Cite
|
Sign up to set email alerts
|

Is there a higher prevalence of tinnitus in patients with temporomandibular disorders? A systematic review and meta‐analysis

Abstract: The aim of this study was to determine whether there exists a higher prevalence of tinnitus in patients with temporomandibular disorders (TMDs) than in patients without TMDs. A systematic review was conducted in PubMed/MEDLINE for articles published between January 1992 and April 2018 in accordance with the PRISMA statement. Studies were included in this review only if they assessed TMDs using the research diagnostic criteria (RDC)/TMD or DC/TMD. A total of five studies were included in the systematic review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…A meta-analysis reviewed five studies which used RDC/TMD for TMJ evaluation; they found that the prevalence of tinnitus was higher in patients with TMDs (35.8%-60.7%) than in patients without TMDs (9.7%-26.0%). The odds ratio of suffering from tinnitus among patients with TMDs was 4.45 [20]. Similar findings were observed by Stephan et al, who further concluded that ENT symptoms were found to be more common in patients who presented myofascial pain and less in those with intra-articular disc disorder [21].…”
Section: Prevalence Of Cross Symptomssupporting
confidence: 80%
“…A meta-analysis reviewed five studies which used RDC/TMD for TMJ evaluation; they found that the prevalence of tinnitus was higher in patients with TMDs (35.8%-60.7%) than in patients without TMDs (9.7%-26.0%). The odds ratio of suffering from tinnitus among patients with TMDs was 4.45 [20]. Similar findings were observed by Stephan et al, who further concluded that ENT symptoms were found to be more common in patients who presented myofascial pain and less in those with intra-articular disc disorder [21].…”
Section: Prevalence Of Cross Symptomssupporting
confidence: 80%
“…Interestingly, prevalence of tinnitus in patients with TMJ disorders reaches 60% in comparison to 15–30% in patients with no TMJ disorder (Chole and Parker, 1992; Tuz et al, 2003). The association between tinnitus and TMJ disorders was confirmed by two recent systematic reviews that reported a significant association between the two conditions in the majority of the identified studies (Bousema et al, 2018; Mottaghi et al, 2019). Both reviews assessed the quality of the included studies.…”
Section: Introductionmentioning
confidence: 62%
“…Bousema et al (2018) evaluated 22 studies which investigated the presence of cervical spine disorders (CSDs) or TMJ disorders in patients with and without tinnitus, or the presence of tinnitus in patients with and without TMJ disorders. In contrast, Mottaghi et al (2019) evaluated findings from just five studies comparing patients with and without TMJ disorders.…”
Section: Introductionmentioning
confidence: 99%
“…© 2019 Polish Dental Association than two symptoms of TMD (compared to 35% of patients in a tinnitus-free control group) and that among TMD patients from 7% to 60% had tinnitus, according to different studies [24]. Higher prevalence of tinnitus in TMD patients was also observed in other studies, supporting the hypothesis that TMD may play a causal role in the development of tinnitus [2,16]. However, it seems that there are no significant patterns of correlation with specific TMD [13].…”
Section: R E V I E W Pa P E Rmentioning
confidence: 55%
“…During examination of the patient the doctor should take into consideration any possible sources of deep pain and symptoms of TMD. If there is coexistent TMD and tinnitus, successful treatment of the former is likely to resolve or at least alleviate the patient's perception of tinnitus [3,16,21,23,24]. Selection of proper therapy should mainly depend on the coexistent TMD, maintaining the rule: "conservative therapy first".…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%